Utilization of adequately iodized salt and its associated factors in Tanzania rural areas: a case of Kilwa district, Lindi region, 2023 - David Mahwera; Rose Msaki; Rogath Kishimba; Fatma Abdallah; Danford Mahwera; Vicent Assay; George Mrema; Geofrey Mchau; Germana Leyna; Theresia Ambrose (PLoS ONE, 2025)
This study assessed household utilization of adequately iodized salt and its associated factors in Kilwa district, Tanzania, where utilization remains low, especially in areas with local salt production. Using a cross-sectional design, 493 households were systematically sampled and interviewed, with 14 local salt producers purposively recruited for in-depth interviews; onsite iodine rapid tests and laboratory analyses determined salt iodine content. Results showed only 9.4% of households used adequately iodized salt. Factors significantly associated with utilization included family size of five or fewer members (AOR = 3.49; 95% CI: 1.62–7.54), good knowledge about iodized salt (AOR = 4.97; 95% CI: 2.04–12.11), storage of salt in dry areas (AOR = 4.44; 95% CI: 1.51–13.07), exposure of salt to sunlight (AOR = 0.29; 95% CI: 0.10–0.85), and salt staying less than two months (AOR = 2.34; 95% CI: 1.10–5.00). Key reasons for low availability of iodized salt included poor protection at production sites, supply of non-iodized salt, lack of training for local producers, community preference for non-iodized salt, and presence of multiple local salt producers. The findings indicate that the prevalence of iodized salt use is very low in Kilwa, with factors such as family size, knowledge, storage practices, sunlight exposure, and salt duration influencing utilization. The study recommends intensified government awareness campaigns to improve knowledge and practices related to iodized salt use, alongside interventions to enhance salt quality and availability at production sites.